Discrimination reported by people with schizophrenia: cross-national variations in relation to the Human Development Index - P. C. Gronholm; S. Ali; E. Brohan; G. Thornicroft (Cambridge University Press, 2023)
Abstract Aims Mental health related stigma and discrimination is a universal phenomenon and a contributor to the adversity experienced by people with schizophrenia. Research has produced inconsistent findings on how discrimination differs across settings and the contextual factors that underpin these differences. This study investigates the association between country-level Human Development Index (HDI) and experienced and anticipated discrimination reported by people with schizophrenia. Methods This study is a secondary data analysis of a global cross-sectional survey completed by people living with schizophrenia across 29 countries, between 2005 and 2008. Experienced and anticipated discrimination were assessed using the Discrimination and Stigma Scale (DISC-10). Countries were classified according to their 2006 HDI. Negative binomial and Poisson regression analyses with a robust standard errors approach were conducted to investigate associations between country-level HDI and discrimination. Results In the regression analyses, no evidence was found for a linear association between HDI and experienced or anticipated discrimination. Further exploratory analyses showed a significant non-linear association between HDI ratings and experienced discrimination. Participants in "high" and "very high" HDI countries reported more experienced discrimination compared to those in "medium" HDI countries. Conclusions HDI does, to some extent, appear to be associated with how far discrimination is experienced across different contexts. More high-quality cross-national research, including research focused on "medium" and "low" countries, is needed to substantiate these findings and identify underlying factors that may explain the pattern observed for experienced discrimination, including generating new datasets that would enable for these analyses to be repeated and contrasted with more recent data. An in-depth understanding of these factors will further aid the adaptation of cross-cultural and context specific anti-stigma interventions in future.